THE EFFECTIVENESS OF SCIENCE STUDENT WORKSHEET WITH COGNITIVE CONFLICT STRATEGIES TO REDUCE MISCONCEPTION ON HEAT CONCEPT - Heny Ekawati Haryono (JURNAL PENA SAINS, 2018)
This study aimed to determine the effectiveness of science worksheets with cognitive conflict strategies to reduce student heat misconceptions. This research was conducted at SMP Negeri 1 Lamongan by using one group pretest-posttest design. The data obtained in this study is quantitative data, and the number of students in VII grade is 50, students are called to complete the research if the proportion of correct answers is more significant than the standard achievement test. While the class is said to complete the study if 85% of students can reach the standard test criteria. The researcher obtained information about the level of mastery of students' concepts by using N-gain, one method in the descriptive qualitative analysis. It shows the different levels of student mastery before and after treatment given. The effectiveness of the Science Worksheet will be analyzed from the acquisition of learning outcomes. This yields 0.94 points which means that the value of N-Gain is in the sufficient category, it can be said that the application of the Science Worksheet with cognitive conflict strategies can reduce heat misconceptions of junior high school students.